Optimization of alkaline activator / fly ash ratio on the compressive strength of manufacturing fly ash-based geopolymer - Mohd Mustafa Al Bakri, Abdullah (Trans Tech Publications, 2012)
Link to publisher's homepage at http://www.ttp.net/